Carbon footprint calculator for Malaysia green highway index - Hafifi, C. M. F. (2019)
The large-scale transportation infrastructure construction in developing countries such as Malaysia requires emission estimation method for better calculation. The aim of this paper is to estimate the carbon footprint emission in the unit of ton of carbon dioxide equivalents (t CO2e/km-lane). This study proposed a life cycle assessment method to estimate the carbon footprint (CO2e) emission based on bridge work under construction in expressway of Malaysia. The results show that highest carbon footprint is from construction of pier column 5.3864 t CO2e/pier column. Because due to highest volume of structural with 12 m depth and 1500 mm cylinder size. The result followed by construction of pile, crosshead, pile cap, beam launching, parapet wall and slab deck at 3.5396, 3.5124, 2.6354, 0.1975, 0.0648, 0.0236 t CO2e/unit respectively. In the sources, emission from onsite construction machinery produce the highest carbon footprint 2.7566 t CO2e/unit, followed by emission production of raw material and transportation of material, 0.3309 and 0.0778 CO2e/pier column respectively. The result in this study can be considered as references for carbon footprint calculator to calculate emission in other expressway of Malaysia.